Physical and Chemical Characteristics of Cookies Based on Modified Janten Banana Flour with Cassava Starch Substitution - Zukryandry Zukryandry; Widia Rini Hartari; Maryanti Maryanti; Febrina Delvitasari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Cookies are one of the most popular food products, widely favored for their crunchy texture and distinctive taste. However, their formulation generally relies on wheat flour, which limits the diversification of local food resources. This study was conducted to evaluate the effect of substituting modified janten banana flour with cassava starch on the physicochemical characteristics of cookies. Treatments consisted of various proportions of banana flour and cassava starch. Analyses included moisture, ash, protein, fat, carbohydrate, and dietary fiber contents, while the physical properties examined were texture (hardness) and color (L, a, b*, and whiteness index). The results showed that increasing the proportion of banana flour significantly affected the quality of cookies. Physically, higher banana flour substitution resulted in darker cookie color, lower whiteness index values, and increased hardness. Chemically, the use of banana flour increased ash, dietary fiber, and carbohydrate contents but reduced fat content, while protein content remained relatively stable. Formulations with 40% cassava starch + 60% banana flour and 20% cassava starch + 80% banana flour provided the best balance of quality and thus have potential for consumer acceptance. These findings emphasize the attractiveness of modified banana flour as an alternative raw feed-stock for healthy and functional cookies, while contributing to local food diversification too.